P299 Inter-individual variability and intra-individual reliability of iTBS-induced neuroplasticity mechanisms in the healthy brain. Issue 3 (March 2017) - Schilberg, L.; Schuhmann, T.; Sack, A.T.
Abstract : Introduction: Neuroplasticity refers to either cortical reorganization or changes in synaptic efficacy between neurons. We combined patterned TMS (iTBS) with electromyography (EMG) to assess and characterize inter-individual variability and intra-individual reliability of TMS-induced neuroplasticity mechanisms in the healthy brain. In the future, reliable measures of TMS-induced neuroplasticity mechanisms could serve as early biomarkers of aberrant cortical neuroplasticity and they could help to guide therapeutic progress of affected individuals. Objectives: To investigate both (1) inter-individual variability and (2) intra-individual reliability of iTBS-induced changes in corticospinal excitability, and (3) the association of individual prolonged measures of corticospinal excitability with iTBS-induced changes in motor evoked potential (MEP) amplitudes. Patients & methods: We applied iTBS over the primary motor cortex (M1) to induce LTP-like mechanisms in fourteen participants on two separate visits and we used EMG from the first dorsal interosseous (FDI) muscle to measure changes in TMS-elicited MEP amplitudes over sixty minutes. We applied sham-iTBS to measure unmodulated prolonged corticospinal excitability. Results: Over a grand period of sixty minutes iTBS led to a group increase of corticospinal excitability, whereas sham-iTBS had no modulatory effects. This increase was reduced on a second measurement (Fig. 1 ) and individual measures had low reliability (Fig. 2 ). Furthermore, individual measures of corticospinal excitability over a prolonged time period (sham-visit) of up to sixty minutes were not associated with the measures of iTBS-induced changes in MEP amplitude of both stimulation visits. Conclusion: At the group level iTBS over M1 has a facilitatory effect on corticospinal excitability. However, this group effect appears to weaken during a second assessment. Furthermore, we find that there is high inter-individual variability and low intra-individual reliability of the observed iTBS-induced neuroplasticity measures. This creates great challenges for the interpretation of group iTBS effects on corticospinal excitability and it is thus difficult to define general characteristics of neuroplasticity mechanisms that are reliably transferable to the individual level.